2011
DOI: 10.4103/0971-5916.92629
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing adherence to antiretroviral therapy

Abstract: HIV has now become a manageable chronic disease. However, the treatment outcomes may get hampered by suboptimal adherence to ART. Adherence optimization is a concrete reality in the wake of ‘universal access’ and it is imperative to learn lessons from various studies and programmes. This review examines current literature on ART scale up, treatment outcomes of the large scale programmes and the role of adherence therein. Social, behavioural, biological and programme related factors arise in the context of ART … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 88 publications
2
51
1
1
Order By: Relevance
“…Poor adherence meant patient not consistent with medical recommendations (>1 missed medication in a month). Patients whose medical reports pointed out one or more missed doses (forgetting of skipping medication) within a month were considered showing poor adherence [11].…”
Section: Study Variablesmentioning
confidence: 99%
“…Poor adherence meant patient not consistent with medical recommendations (>1 missed medication in a month). Patients whose medical reports pointed out one or more missed doses (forgetting of skipping medication) within a month were considered showing poor adherence [11].…”
Section: Study Variablesmentioning
confidence: 99%
“…7,8 From the available evidence, an average rate of 24.8% of nonadherence to medication has been reported in most of the patients having chronic diseases 9 ; however, the level of ART adherence among PLHIV is higher compared to most of the other chronic diseases. 10 Previously published studies reported multiple barriers for optimal adherence to ART in both developed and developing countries, [11][12][13][14] which could be categorized into patient-related, medication-related, and health system-related factors. 15 As these barriers vary across settings, identification of the factors responsible for nonadherence to ART and contextualization of these factors will be helpful in designing and developing intervention strategies to improve adherence to ART.…”
Section: Introductionmentioning
confidence: 99%
“…Adherence in our study was defined as intake of a minimum of 95% of pills which were expected to be taken by the person with HIV, which is as defined by National AIDS Control Organization, India [17]. As per existing literature, HIV associated neurocognitive deficits increase the risk of non-adherence in HIV.…”
Section: Hiv Treatment Variablesmentioning
confidence: 99%